Childhood Socioeconomic Status and Depressive Symptoms of Young Adults: Mediating Role of Childhood Trauma - Yang, Caiyan; Chen, Peiyi; Xie, Junyi; He, Yongtong; Wang, You; Yang, Xueling (Frontiers in Psychiatry, 2021)
Background: Studies have shown that low childhood socioeconomic status (SES) is associated with a high prevalence of depressive symptoms. Childhood trauma, as a potential consequence of low SES, may play an important part, but the mediation effect of childhood trauma remains to be elucidated. Methods: A cross-sectional survey was conducted among 1,807 university students. The MacArthur Scale of Subjective Social Economic Status—Youth Version, Childhood Trauma Questionnaire, and Beck Depression Inventory were used to measure childhood SES, childhood trauma, and current depressive symptoms, respectively. A structural equation model (SEM) was employed to demonstrate the mediating role of childhood trauma on the association between childhood SES and depressive symptoms. Results: The SEM demonstrated that childhood SES had significant indirect effects upon depressive symptoms via childhood trauma. Childhood trauma accounted for 89.3% of the total effect, indicating a profound mediation effect. Conclusions: The effect of childhood SES on the depressive symptoms of young adults was mediated by childhood trauma, which emphasizes the importance of early prevention and intervention of child neglect/abuse.